SAT-LB1 Detection of Serum Macro-Luteinizing Hormone - Ogura-Ochi, Kanako (J Endocr Soc, 2020)
Macromolecules of prolactin (PRL) and thyrotropin (TSH), so called macro-PRL and macro-TSH, respectively, are rarely detected in the patients’ serum containing high concentrations of these hormones. The macromolecules are involved in increasing the serum concentrations due to aggregation with the autoantibodies in serum. Here we show a case having macromolecules of luteinizing hormone (LH), possibly due to the complex to immunoglobulin-G (IgG). A 35-year-old Japanese female who has complained menstrual irregularity and had a past surgical history of thyroid cancer was referred to our hospital. Laboratory examination showed an extremely high concentration of serum LH (>200 mIU/ml), while serum levels of follicle-stimulating hormone, estradiol, thyroid hormones, human chorionic gonadotropin, testosterone, and prolactin were all within the normal ranges. MRI study showed a normal pituitary shape without any tumorous lesion. Responses of gonadotropins to LH-releasing hormone (LHRH) stimulation were marginally blunted but showed an LH-dominant pattern such as polycystic ovary syndrome. We suspected the presence of macro-LH because of the divergence between the clinical features and the LH level. Of note, the recovery rate of LH levels after precipitation with polyethylene glycol (PEG) was less than 5%, and the gel-filtration analysis further demonstrated an LH peak slightly earlier fraction than IgG. One case report documented the presence of macro-LH in the serum from a young female patient complicated with autoimmune thyroiditis, suggesting the formation of macro-LH related to some latent autoimmune diseases. To assume macro-LH and to re-examine LH levels after serum precipitation by PEG or protein A/G and fractionation are important to avoid unnecessary treatment to increased LH conditions. In clinical practice, we should suspect the presence of macro-LH, if serum LH levels are unexpectedly high compared to the clinical signs.